Early and late changes in endothelial dependent vascular relaxation and contraction responses in the microcirculation of diabetic rats - Munisamy, Seetha A/P (2020)
Diabetes is associated with micro and macrovascular complications which contributes to endothelial dysfunction (ED) and leads to cardiovascular diseases. ED is characterized by impairment of endothelium-dependent relaxation and increases in endothelium-dependent contraction. The endothelial cells release factors that cause endothelial relaxation and contraction. The role of these factors in the microvasculature of diabetes is not well characterized. There were three main objectives of this study; firstly, to determine the contribution of nitric oxide (NO), prostacyclin, endothelium-dependent hyperpolarization (EDH) and thromboxane (TXA2) receptor in endothelium-dependent relaxation and contraction in the microcirculation of diabetic rats; secondly, to determine the expression of enzymes and receptors involved in mediating endothelial responses and finally to determine the early (2 weeks) and late changes (10 weeks) in the functional and molecular responses in the microcirculation of diabetes rats. This study consisted of four experimental groups; normal 2-week rats, diabetic 2-week rats, normal 10-week rats and diabetic 10-week rats (n=15 rats per group). Vascular function studies were performed using wire myography. The contributions of individual EDRF (NO, prostacyclin and EDH) and TXA2 receptor in mediating endothelium-dependent relaxations and contractions were evaluated in tail arteries of all the experimental groups. The expressions and distributions of endothelial nitric oxide synthase (eNOS), cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), prostacyclin synthase (PGIS), prostacyclin (IP) receptor, TXA2 receptor and TXA2 synthase proteins were determined by Western blotting and immunohistochemistry. Endothelium-dependent relaxations were significantly decreased in diabetic 2-week [Rmax; 73.49 (11.04) % vs 89.32 (10.03) %, p=0.002] and diabetic 10-week rats [Rmax; 58.84 (18.79) % vs 89.32 (10.03) %, p<0.01], respectively compared with normal 2-week rats. NO-mediated relaxations were attenuated in diabetic 10-week rats compared with normal 2-week (p<0.001) and normal 10-week rats (p<0.001). EDH-mediated relaxations were lower in diabetic 10-week rats compared to normal 2-week rats (p=0.012) and normal 10-week rats (p=0.017). Diminished relaxations to prostacyclin were seen in diabetic 10-week rats compared to normal 2-week (p<0.001) and diabetic 2-week rats (p=0.033). Western blotting and immunostaining showed that diabetes reduced expression of eNOS, IP receptor and PGIS proteins in rat tail arteries. For endothelium-mediated contractions, significant increase in endothelium-dependent contractions were seen in diabetic 10-week rats [Emax; 113.73 (51.32) % vs 34.80 (21.00) %, p<0.001], with a trend of increase in diabetic 2-week rats [Emax; 71.80 (46.02) % vs 34.80 (21.00) %, p<0.058] compared to normal 2-week rats. Significant increases in both COX-1 and COX-2 mediated contractions, and TXA2 receptor mediated contractions were seen in diabetic 10- week rats. Trend of increased expression of COX-2 and TXA2 receptor proteins were observed in diabetic 10-week rats supporting the findings of functional studies. In conclusion, impairment in microvascular endothelium-dependent relaxations and increased endothelium-dependent contractions were observed in diabetic rats, and this worsened by prolonged diabetes. Therefore, early prevention is necessary to manage ED which may be reversible at an early stage of diabetes.